The effect of digital game addiction on physical activity and sleep habits in secondary school students - Marufoğlu, Semra; Kutlutürk, Seval (Journal of Dependence, 2021)
Objectıve: The aim of this study is to investigate the effect of digital game addiction on physical activities and sleep habits of secondary school students. Method: The study was conducted on 100 middle school students (F: 56, M: 44) who were 5th, 6th, 7th and 8th grades. Students’ digital game addiction was evaluated by the Digital Game Addiction Scale for Children (DGAS-C), physical activity levels was evaluated by the Primary School Students’ Physical Activity Questionnaire (PAQ), sleep habits was evaluated by Children’s Sleep Habits Questionnaire (CSHQ). Results: There was no statistically significant relationship between DGAS-C and its subgroups and FAQ). There was no statistically significant difference between students’ digital play and sleep habits. Students who played digital games for more than 3 hours and more than 3 hours were found to have higher levels of digital game addiction compared to other students. Fifth grade students were found to have higher physical activity levels than 7th and 8th grade students. Conclusion: In this study, no relationship was found between digital game addiction and physical activity and sleep habits of secondary school students. These results may be due to the fact that students’ access to digital tools is under parental control and limited access of children to digital game tools for economic reasons.